Forty-Year Trends in Cardiac Implantable Electronic Device Infective Endocarditis. (14th October 2022) - Hernández-Meneses, Marta; Llopis, Jaume; Sandoval, Elena; Ninot, Salvador; Almela, Manel; Falces, Carlos; Pericàs, Juan M; Vidal, Bárbara; Perissinotti, Andrés; Marco, Francesc; Mestres, Carlos A; Paré, Carlos; et al.
Abstract: Background: Studies investigating cardiac implantable electronic device infective endocarditis (CIED-IE) epidemiological changes and prognosis over long periods of time are lacking. Methods: Retrospective single cardiovascular surgery center cohort study of definite CIED-IE episodes between 1981–2020. A comparative analysis of two periods (1981–2000 vs 2001–2020) was conducted to analyze changes in epidemiology and outcome over time. Results: One-hundred and thirty-eight CIED-IE episodes were diagnosed: 25 (18%) first period and 113 (82%) second. CIED-IE was 4.5 times more frequent in the second period, especially in implantable cardiac defibrillators. Age (63 [53-70] vs 71 [63–76] years, P < .01), comorbidities (CCI 3.0 [2–4] vs 4.5 [3–6], P > .01), nosocomial infections (4% vs 15.9%, P = .02) and transfers from other centers (8% vs 41.6%, P < .01) were significantly more frequent in the second period, as were methicillin-resistant coagulase-negative staphylococcal (MR-CoNS) (0% vs 13.3%, P < .01) and Enterococcus spp. (0% vs 5.3%, P = .01) infections, pulmonary embolism (0% vs 10.6%, P < .01) and heart failure (12% vs 28.3%, p < .01). Second period surgery rates were lower (96% vs 87.6%, P = .09), and there were no differences in in-hospital (20% vs 11.5%, P = .11) and one-year mortalities (24% vs 15%, P = .33), or relapses (8% vs 5.3%, P = 0.65). Multivariate analysis showed Charlson index (hazard ratios [95% confidence intervals]; 1.5 [1.16–1.94]) and septic shock (23.09 [4.57–116.67]) were associated with a worse prognosis, whereas device removal (0.11 [.02–.57]), transfers (0.13 [.02–0.95]), and second-period diagnosis (0.13 [.02–.71]) were associated with better one-year outcomes. Conclusions: CIED-IE episodes increased more than four-fold during last 40 years. Despite CIED-IE involved an older population with more comorbidities, antibiotic-resistant MR-CoNS, and complex devices, one-year survival improved. Abstract : Cardiac implantable electronic device infective endocarditis (CIED-IE) episodes increased >4-fold during the last 40 years. In the 2 most recent decades, despite CIED-IE involving an older population with more comorbidities, antibiotic-resistant microorganisms, and complex devices, 1-year survival has improved.